Facile synthesis of 5,6-dihydro-5-hydroxy-2(1H)-pyridone - Upadhyay, Puspesh K.; Prasad, Rajendra; Pandey, Menaka; Kumar, Pradeep (Tetrahedron Letters, 2009)
A short synthesis of 5,6-dihydro-5-hydroxy-2(1H)-pyridone was achieved from L-serine employing Horner-Emmons olefination as the key step. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: alkaloids; Horner-Emmons olefination; L-serine; Pyridone; Z-selectivity